Adipose-derived mesenchymal stem cells protect endothelial cells from hypoxic injury by suppressing terminal UPR in vivo and in vitro - Keese, Michael; Zheng, Jiaxing; Yan, Kaixuan; Bieback, Karen; Yard, Benito A.; Pallavi, Prama; Reißfelder, Christoph; Kluth, Mark Andreas; Sigl, Martin; Yugublu, Vugar (International journal of molecular sciences, 2023)
Adipose-derived stem cells (ASCs) have been used as a therapeutic intervention for peripheral artery disease (PAD) in clinical trials. To further explore the therapeutic mechanism of these mesenchymal multipotent stromal/stem cells in PAD, this study was designed to test the effect of xenogeneic ASCs extracted from human adipose tissue on hypoxic endothelial cells (ECs) and terminal unfolded protein response (UPR) in vitro and in an atherosclerosis-prone apolipoprotein E-deficient mice (ApoE−/− mice) hindlimb ischemia model in vivo. ASCs were added to Cobalt (II) chloride-treated ECs; then, metabolic activity, cell migration, and tube formation were evaluated. Fluorescence-based sensors were used to assess dynamic changes in Ca2+ levels in the cytosolic- and endoplasmic reticulum (ER) as well as changes in reactive oxygen species. Western blotting was used to observe the UPR pathway. To simulate an acute-on-chronic model of PAD, ApoE−/− mice were subjected to a double ligation of the femoral artery (DLFA). An assessment of functional recovery after DFLA was conducted, as well as histology of gastrocnemius. Hypoxia caused ER stress in ECs, but ASCs reduced it, thereby promoting cell survival. Treatment with ASCs ameliorated the effects of ischemia on muscle tissue in the ApoE−/− mice hindlimb ischemia model. Animals showed less muscle necrosis, less inflammation, and lower levels of muscle enzymes after ASC injection. In vitro and in vivo results revealed that all ER stress sensors (BIP, ATF6, CHOP, and XBP1) were activated. We also observed that the expression of these proteins was reduced in the ASCs treatment group. ASCs effectively alleviated endothelial dysfunction under hypoxic conditions by strengthening ATF6 and initiating a transcriptional program to restore ER homeostasis. In general, our data suggest that ASCs may be a meaningful treatment option for patients with PAD who do not have traditional revascularization options.
Gesehen am 09.04.2024